2020
DOI: 10.3390/molecules25071505
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sp. FPF-1 Produced Keratinase with High Potential for Chicken Feather Degradation

Abstract: Chicken feathers are predominantly composed of keratin; hence, valorizing the wastes becomes an imperative. In view of this, we isolated keratinase-producing bacteria and identified them through the 16S rDNA sequence. The process condition for keratinase activity was optimized, and electron micrography of the degradation timelines was determined. Keratinolytic bacteria were isolated and identified as Bacillus sp. FPF-1, Chryseobacterium sp. FPF-8, Brevibacillus sp. Nnolim-K2, Brevibacillus sp. FPF-12 and Brevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…Preparation of powdered chicken feather (PCF) substrate utilized in this study followed a similar approach as we reported previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of powdered chicken feather (PCF) substrate utilized in this study followed a similar approach as we reported previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The media nitrogen and carbon quotient influence microbial protease secretion and, keratinous proteins are inassimilable to microbial cells due to their structural complexity; therefore, production of elaborate keratinolytic enzymes may be regulated in response to media constituents (Riffel et al, 2011;Nnolim et al, 2020a). Worthy of note is the fact that several reports attributed unitary secreted enzymes to the complete degradation of keratin, thus controverting the position of cooperative enzyme actions.…”
Section: Keratin Biodegradation -The Keratinase and Disulfide Reductamentioning
confidence: 99%
“…The maintenance of homeostatic balance in extreme situations, utilization of all known material (macro and micro), and elements as sources of energy and, or cellular building tools, are attributable to the diversity of the genome and the complexity of the microbial expression systems (Francino, 2012). Keratinases, are inducible enzymes that allow the producer microbe to utilize the keratinous biomass as a nutrient source (Gupta and Ramnani, 2006;Nnolim et al, 2020a), and the process occurs only in the presence of keratinous biomass and the absence of readily available nutritional reference; hence, keratinase production only kick-starts out of necessity. The exudation of keratinase offers microbes the opportunity to utilize a broad spectrum of proteinaceous substrates, thus promoting organic matter recycling in all ecological milieu (Bohacz and Korniłłowicz-Kowalska, 2019).…”
Section: Environmental Impact Of Keratinous Waste and The Ecological mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the imperative for a reliable alternative motivates for the exploration of highly abundant renewable resources for sustainable products. The potentials locked in carbonoclastic materials account for the desire to valorize waste biomass into high-value products, and that ensures sustainability in economic development (Akinsemolu 2018 ; Nnolim et al 2020a ). The agro and food industry generates lots of solid wastes which may suitably feed into the economy with novel valorization approach.…”
Section: Introductionmentioning
confidence: 99%